Going Online - is the World Ready to Replace Litigation with Online Dispute Resolution Mechanisms? - Ziemblicki, Bartosz (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
The increase of people’s activity in the cyberspace results in a need to provide dispute resolution services online. Even though ODR is about 15 years old, until today no provider of such services has been successful in creating universal dispute resolution system. ODR has got many advantages over traditional ADR and state court litigation. They include low cost, flexibility, avoidance of jurisdiction and choice of law problems and above all speed. However there are also disadvantages, which prevent Internet users from putting trust in this method of dispute resolution. They include issues concerning authenticity, confidentiality, accessibility and due process rights. The first serious attempts to establish ODR systems were initiated by academics. They did not last long though. The most successful attempts include eBay and ICANN systems. They have, however, a limited scope of application. The first one deals only with simple, one-issue, low cost, e-commerce, consumer transaction and its outcome, at least formally, is not binding. The other is praised for effective enforcement without reference to state courts, but it deals only with Internet domain disputes and provides no other remedies than assigning those domains to the winning party. Overall ODR is destined to be successful sooner or later.
Keywords: cyberprzestrzeń; Internetowe rozwiązywanie sporów (ODR); konsumenci